Efforts to Improve the Ability to Identify the Structure and Linguistic Elements of the Explanation Text using the Problem Based Learning (PBL) Model for VIII Class Students - Finondang Roselina Pangaribuan (Indonesian Journal of Education and Mathematical Science, 2022)
This classroom action research aims to describe the increase in the ability to identify the structure and elements of the explanatory text language using the problem-based learning (PBL) model for class VIII students of SMP Negeri 2 Parmonangan for the 2020/2021 academic year. Based on observations, the ability of students of SMP Negeri 2 Pamonangan in terms of identify structures and language elements is still low. This is evidenced by the specified minimum completeness criteria value of 75 which has not been achieved. Classically completeness with data that the final score of students from learning outcomes is still much below the minimum completeness criteria (KKM). If the percentage is not more than 70%. Based on the implementation in 3 cycles, the research hypothesis is obtained as follows "There is an increase in the skills to identify the structure and elements of the explanatory text language of students in class VIII SMP Negeri 2 Parmonangan Tapanuli Utara with a problem-based learning (PBL) learning model." This can be seen in the results of data analysis on learning outcomes in each cycle that has increased. Cycle 1, the average value of 73.7 classical absorptions of 73.7%, and classical learning completeness of 66.7%. Cycle II average value of 78.8, classical absorption. In cycle III, the average value is 80.5. This means that the students' learning completeness value at SMP Negeri 2 Parmonangan Tapanuli Utara increased.